Supplementation of Methionine or Choline Did Not Improve Health or Growth Performance in High-Risk, Newly Received Beef Heifers - Madeline S. Grant; Dale A. Blasi; Evan C. Titgemeyer (Kansas Agricultural Experiment Station Research Reports, 2024)
Objective:This study was conducted to determine if supplemental methionine or choline improves health or growth performance in high-risk, newly received beef heifers. Study Description:In a 3-year experiment, 1,440 beef heifers (480 per year; 493 lb initial weight; Tennessee origin) were received in 15 truckloads (five per year) in October of 2020, 2021, and 2022. Heifers were limit-fed in 60-day receiving trials to evaluate the effects of supplemental methionine or choline on health and growth performance. Cattle received one of five treatments: control (no added methionine or choline); 5 or 15 g/day available methionine (8.33 or 25 g/day Smartamine M; Adisseo USA Inc., Alpharetta, GA; ruminally protected methionine); or 1.17 or 3.5 g/day available choline (26 or 78 g/day ReaShure; Balchem Corp., Montvale, NJ; ruminally protected choline). Results:Small differences among treatments were observed for final body weight, average daily gain, and gain:feed (P ≤ 0.10), but none of the treatments differed from the control. No differences among treatments were observed for respiratory morbidity or mortality (P≥ 0.30). The Bottom Line:Supplemental methionine or choline did not affect health or growth performance of high-risk, newly received heifers.
Keywords: methionine; choline; receiving cattle